Glass Bead-Assisted Fine Dispersion of Multi-walled Carbon Nanotube in Silicone Matrix II: Effect on the Viscosity of Silicone Rubber - Park, Eun Young; Lim, Sung Wook (Asian Journal of Chemistry, 2013)
Electrically conducting silicone rubber composites were prepared by the incorporation of conducting fillers including carbon black, carbon fibers and carbon nanotubes. Silicon/multi-walled carbon nanotube (MWCNT) composites were produced by mechanical mixing. Glass beads (GBs) were introduced to significantly improve the dispersion of MWCNTs in the silicone matrix. The dispersion of MWCNTs in a silicone matrix is related to the ball-bearing effect of the glass beads. The electrical conductivity of the high viscosity-silicone/MWCNT/GB composite was approximately double that of the composite without glass beads due to the improved distribution uniformity of MWCNTs in the silicone matrix. In addition, the presence of glass beads in the silicone matrix improved the mechanical properties, such as the tensile strength and elongation at break as well as the electrical conductivity.